The Effect of Earnings Volatility on Borrowers' Cost of Debt: Evidence from Indonesia - Goldia Liku Sirupang Pongrangga; Anggreni Dian Kurniawati (Media Ekonomi dan Manajemen, 2020)
This study aimed to examine the effect of earnings volatility on borrowers cost of debt. In addition, this study also analyzes the difference effect of earnings volatility on borrowers cost of debt for different industries. Samples were selected by using the purposive sampling method and obtained 1,100 observations from eight industries sector in Indonesia listed in Indonesian Stock Exchange based on the Jakarta Stock Industrial Classification from 2012-2016. Three control variables used in this study were profitability, liquidity and solvency. The result shows that earnings volatility has positive effect on the borrowers cost of debt. The profitability has a negative effect on borrowers cost of debt, nevertheless liquidity and solvency have no effect on borrowers cost of debt. Therefore, every company expected to maintain and stabilize their earnings with generates a good performance of profitability. Furthermore, the result also shows that there is a difference effect of earnings volatility on borrowers cost of debt in each industrial sector in Indonesia listed in Indonesia Stock Exchange. The industrial sector which have significant effects between earnings volatility and borrowers cost of debt were agriculture sector and miscellaneous sector.